Aspects of micro-tactile dynamic sensor tracking - Weckenmann, Albert; Schuler, Alexander (International Journal of Nanomanufacturing, 2012)
To reduce measurement deviations of tactile surface measurement systems resulting from high surface angles, a probing principle is investigated based on a dynamic surface slope dependent sensor tip rotation. To research the principle, a simulation environment and methods to calculate an optimal tip rotation angle are developed. The achievable deviation reduction of the principle and the performance of the different angle determination methods are examined based on different sample surfaces. In support of a hardware realisation, parameters of a virtual rotation system are varied, its effectiveness is quantified and the limits are identified. Copyright © 2013 Inderscience Enterprises Ltd.
UnivIS-Import:2015-03-09:Pub.2012.tech.FT.FT-QMFMT.aspect
Keywords: Measurement deviation; Profilometry; Rotation; Simulation

Construction and evaluation of a traceable metrological scanning tunnelling microscope - Hoffmann, Jörg; Schuler, Alexander; Weckenmann, Albert (Measurement, 2009)
Scanning tunnelling microscopy enables for imaging of conductive surfaces with a resolution down to the atomic level. However, virtually all commercial scanning tunnelling microscopes use piezo tube scanners and capacitance gauges what limits the operating range to typically less than 100 μm in the scanning axes and 10 μm in probing direction. Traceability of measured dimensions to the length unit metre can only be ensured by frequent calibration with the help of standards for pitch and step height. To improve the metrological characteristics of the measurement technique scanning tunnelling microscopy and to broaden its field of application, a directly traceable long range metrological scanning tunnelling microscope was set-up using a laser-interferometrically controlled nanopositioning unit with an operating range of 25 · 25 · 5 mm3 as scanner and a passive tunnelling current measuring probing system as a null indicator. Line scan repeatability of 5 nm has been achieved at 1 nm vertical resolution. © 2009 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2009.tech.FT.FT-QMFMT.constr
Keywords: Scanning tunnelling microscopy; Surface metrology; Traceability

Construction and evaluation of a traceable metrological scanning tunnelling microscope (Kurzfassung) - Hoffmann, Jörg; Schuler, Alexander; Weckenmann, Albert (Mechatronik, 2010)
UnivIS-Import:2015-03-09:Pub.2010.tech.FT.FT-QMFMT.constr

Development of a 3D tunneling current probing system for micro- and nano-coordinate metrology - Sun, Zhongyuan; Schuler, Alexander; Hausotte, Tino (12th International Symposium on Measurement Technology and Intelligent Instruments (ISMTII 2015), 2015)
With decreasing structure dimensions and rising aspect ratios of the products the demands for precision measurement of three dimensional micro- and nanogeometries over a large area have increased. Therefore many different nanometre resolving 3D capable probing sensors and corresponding 3D positioning systems to operate the sensors for 3D measurements have been developed to meet such requirements. The mechanical contact-free, electrical work piece probing based on the scanning tunneling microscopy principle offers new possibilities for 3D micro coordinate measurements as well as for nanometre resolved topography measurements in micro- and nanometrology. This paper introduces an updated version of this probing sensor system extended with a 3D movable piezo scanner to directly detect its probing direction. With the magnitude and the direction of the contact vector forwarded to the position control of the nanopositioning and nanomeasuring machine NMM-1 all of the 3D measurement commands of NMM-1 can be utilized, allowing 3D surface scans and especially 3D free-form surface scans.
Keywords: scanning tunneling microscopy (STM); microCMM; nanoCMM; nanometrology; probing system

Development of a tunnelling current sensor for a long-range nano-positioning device - Weckenmann, Albert; Hoffmann, Jörg; Schuler, Alexander (Measurement Science & Technology, 2008)
Dimensional micro and nano metrology is gaining enormously in importance with the development and advancement of micro mechanics (e.g., micro gears), micro electronic and mechanical devices (e.g., MEMS, miniaturized sensors), micro optics (e.g., cameras in mobile phones) and nanotechnology (e.g., functional surface layers), but effective and efficient quality control in these fields is hindered today by the lack of powerful, flexible, robust and economic tools for nanometre-resolved 3D metrology. Scanning probe microscopy (e.g., AFM) suffers from small measuring ranges, fragility, a lack of flexibility and usually unsatisfactory metrological properties such as repeatability and linearity. Miniaturized tactile 3D coordinate measuring machines (CMMs) today only deliver very low point rates and are not suitable for measuring surface fine structure due to the characteristics of their probing elements and their dynamic properties. Additionally AFM tips tend to wear and micro CMMs may damage the workpiece. To overcome these limitations a laser-interferometrically controlled 3D nano- positioning and measuring machine (NMM-1) with a measurement range of 25 mm × 25 mm × 5 mm and sub-nanometre positioning resolution has been equipped with a custom made current measuring probing system. The use of electrical probing interaction in the nanoampere order instead of force (tactile probing, AFM) gives much more flexibility for size and shape of the probing element, as gravitational influence and stresses in the probe are not relevant for probing performance. The combined system can be used as a metrological long-range scanning tunnelling microscope, but also as a 3D micro CMM and provides nanometre resolution combined with an outstandingly large measuring range of several millimetres and traceable position measurement via three helium-neon (HeNe) laser interferometers. Results of the experimental set-up show that the combination of laser interferometry and electrical probing can deliver a reproducibility of down to 3 nm at ranges of several millimetres. © 2008 IOP Publishing Ltd.
UnivIS-Import:2015-03-09:Pub.2008.tech.FT.FT-QMFMT.develo
Keywords: Nanometrology; Probing system; Scanning tunnelling microscopy

Fibre-optical 3-D measurement of highly curved free-form surfaces - Timmermann, Martin; Weinert, Benedict; Schuler, Alexander; Loderer, Andreas; Hausotte, Tino (15th International Conference on Metrology and Properties of Engineering, 2015)

Measurement strategies in optical 3-d surface measurement with focus variation - Tian, Yingzhong; Weckenmann, Albert; Hausotte, Tino; Schuler, Alexander; He, Bin (Abstracts of the ISMQC 2013, 2013)
Focus variation is an optical contact-free method that allows the measurement of three-dimensional surface metrology using optics with limited depths of field and vertical scanning. It was documented in the ISO 25178-6 first time in 2010.As one method of image capture, it has very crucial influence to get an excellent quality image that some key parameters are selected correctly for different workpiece. Those key parameters are including the exposure time, contrast, filters and so on. In this paper, a few of applications were selected to demonstrate the capabilities of the system using different measurement parameters including measurements on cutting-insert tool, stainless steel ball, stepped workpiece and VDI standard workpiece with silver colour surface. Some principles were concluded for optical three-dimensional surface measurement with focus variation after comparing the practical results with different parameters, serving as measurement strategies.
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.lfmt.measur
Keywords: 3-D Measurement; High precision; Image quality; Parameters optimizing

Micro- and nanocoordinate measurements of micro-parts with 3-D tunnelling current probing - Schuler, Alexander; Hausotte, Tino; Sun, Zhongyuan (Journal of Sensors and Sensor Systems, 2015)
Measurement tasks of modern micro- and nanometrology are posing a problem for current measurement instruments with decreasing structure sizes and rising aspect ratios. There is an open requirement for nanometre-resolving 3-D capable sensors and corresponding 3-D positioning systems to operate the sensors for 3-D measurements. A 3-D probing system based on electrical interaction is presented which is operated on a nanopositioning system type SIOS NMM-1. Furthermore, we demonstrate the progress and new possibilities for 3-D measurements with the nanopositioning and nanomeasurement machine NMM-1 and also with the application of a rotary kinematic chain. In addition new 3-D measurement routines for the NMM-1, also for micro-tactile probing systems as well as current plans, are shown.

Mikrokoordinatenmesstechnik mit elektrischer Werkstückantastung - Weckenmann, Albert; Schuler, Alexander (Technisches Messen, 2009)
UnivIS-Import:2015-03-09:Pub.2009.tech.FT.FT-QMFMT.mikrok

Sensors for accurate geometric measurements in manufacturing - Weckenmann, Albert; Büttgenbach, Stephanus; Tan, Özgür; Schuler, Alexander; et al. (Proceedings Sensor 2009, 2009)
UnivIS-Import:2015-04-16:Pub.2009.tech.FT.FT-QMFMT.sensor

Setup and evaluation of a sensor tilting system for dimensional micro- and nanometrology - Schuler, Alexander; Weckenmann, Albert; Hausotte, Tino (Institute of Physics: Hybrid Open Access, 2014)
Sensors in micro- and nanometrology show their limits if the measurement objects and surfaces feature high aspect ratios, high curvature and steep surface angles. Their measurable surface angle is limited and an excess leads to measurement deviation and not detectable surface points. We demonstrate a principle to adapt the sensor's working angle during the measurement keeping the sensor in its optimal working angle. After the simulation of the principle, a hardware prototype was realized. It is based on a rotary kinematic chain with two rotary degrees of freedom, which extends the measurable surface angle to +/- 90 degrees and is combined with a nanopositioning and nanomeasuring machine. By applying a calibration procedure with a quasi-tactile 3D sensor based on electrical near-field interaction the systematic position deviation of the kinematic chain is reduced. The paper shows for the first time the completed setup and integration of the prototype, the performance results of the calibration, the measurements with the prototype and the tilting principle, and finishes with the interpretation and feedback of the practical results.
Keywords: micrometrology; 3D; form; measurement

Tunnelstromtaster für die Mikrokoordinatenmessung - Hausotte, Tino; Weckenmann, Albert; Schuler, Alexander (VDI-Berichte 2133, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.FT.FT-QMFMT.tunnel

Update on a 3D probing system based on electrical near-field interaction for micro- and nano-coordinate metrology - Sun, Zhongyuan; Schuler, Alexander; Hausotte, Tino (Micro/Nano Manufacturing Workshop, 2015)